2013
DOI: 10.1111/ecot.12030
|View full text |Cite
|
Sign up to set email alerts
|

Happiness, religion and economic transition

Abstract: In an important paper, Lelkes (2006) examines the impact of transition on happiness in Hungary using two Hungarian household survey datasets for the years 1992 and 1998. In particular, Lelkes examines the impact of religious behaviour on self-reported well-being. Using ordered logit models, Lelkes estimates and presents the marginal effect associated with membership in the highest 'fully satisfied' category, and finds that religious people have a consistently higher probability of being 'fully satisfied' than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In other words, ideological freedom increases individual religiosity, which, in turn, affects life satisfaction positively. A recent study extends these findings to more transition economies, including Bulgaria, the Czech Republic, Poland, and Slovakia, and confirms a positive correlation between life satisfaction and religious services attendance in transition economies [8].…”
Section: Starting From Max Weber's Seminal Book the Protestant Ethic mentioning
confidence: 55%
“…In other words, ideological freedom increases individual religiosity, which, in turn, affects life satisfaction positively. A recent study extends these findings to more transition economies, including Bulgaria, the Czech Republic, Poland, and Slovakia, and confirms a positive correlation between life satisfaction and religious services attendance in transition economies [8].…”
Section: Starting From Max Weber's Seminal Book the Protestant Ethic mentioning
confidence: 55%
“…The benchmark regression results suggested that people with religious beliefs had higher levels of depression in China, which was also partially supported by the relevant literature (63,64). But by taking empirical measurements and/or conducting metaanalyses using different measurement scales, samples, databases, and taking data from different countries, religious beliefs, and nations, most related studies had found that religious beliefs and participation in religious behaviors could improve happiness, subjective well-being, and mental health (65)(66)(67)(68)(69)(70)(71)(72)(73). For example, Cohen-Zada and Sander (68) used repeal as an instrumental variable for church attendance and provided direct evidence that church attendance had a significant positive effect on happiness; the study of Kortt et al (66) provided strong evidence of an association between attendance at religious services and life satisfaction in the Australian social context; Van Cappellen et al (71) found that religious beliefs could increase happiness through positive emotions of self-transcendence.…”
Section: The Influence Of Control Variables On the Degree Of Depressionmentioning
confidence: 56%
“…These models are based on the sustainable development of socioeconomic systems and the identification of management tools and indicators that are effective in the regional scope [23,29,[48][49][50][51] or those focused on case studies [11,52]. Those models based on the economic analysis of sustainable development [53] and regional competitiveness based on the grouping of indicators through multicriteria comparisons, such as the analyses carried out by Florea and Florea from the regional economics perspective [54]-in 268 European regions-or those applied to case studies by authors such as Boggia & Cortina [55]. Likewise, the integrated multicriteria strategic planning approaches that in engineering and sustainable development are based on different methodological evaluation tools in order to support adaptive and inclusive decision-making processes that lead public authorities to opt for the most profitable in terms of environmental, social and economic sustainability [7].…”
Section: The Role Of Facilitating Methodologies In Sustainable Territorial Developmentmentioning
confidence: 99%